Development of A Teaching Module on the Material of Constitution and Norms in Society for Grade IV Students Muhammadiyah Elementary School 13 Medan - Cindy Claudia Br Barus (Yayasan Zia Salsabila, 2025)
The problematic phenomenon faced in Civic Education learning at Muhammadiyah 13 Elementary School Medan is the lack of development of teaching modules on the constitution and norms in society. This causes students to experience difficulties in understanding the material, which impacts low active participation and student learning motivation. Therefore, this study aims to develop an effective and interesting teaching module on the constitution and norms in society for fourth grade students. The research method used is Research and Development (R&D) with a 3D development model (Define, Design, Development). This research was conducted at Muhammadiyah 13 Elementary School Medan by involving expert validators to test the validity of the teaching module and responses from teachers and students to measure the practicality of the developed module. The results showed that the developed teaching module met the criteria for very good validity with a percentage of 95% for the language aspect, 96% for the media aspect, and 94% for the material aspect. In addition, the results of the teacher response questionnaire showed a percentage of 96% indicating that the teaching module is very practical to use. Student responses were also very positive, with a practicality percentage reaching 100%. This teaching module has proven effective in improving students' understanding of the constitution and norms in society.